Competing expectations: advance care planning from the perspectives of doctors and nurses in the South-East Asian context - Lall, Priya (2022)
This study qualitatively examines the perspectives of doctors and nurses on the implementation of the Advance Care Planning program in Singapore. Findings suggest that a combination of structural and conceptual factors hindered the performance of ACP. Themes on structural factors indicated that low awareness of ACP among senior staff resulted overall lack of buy-in and incorrect implementation of the program due to misconceptions. Conceptual factors pointed to lack of clarity on intended outcomes or roles. Consequently, participants drew meaning through the prism of their profession, resulting in competing expectations and tensions on possible outcomes of the program.